Robust control of underactuated systems: higher order integral sliding mode approach - ud Din, Sami; Khan, Qudrat; Rehman, Fazal ur; Akmeliawati, Rini (Hindawi Publishing Corporation, 2016)
This paper presents a robust control design for the class of underactuated uncertain nonlinear systems. Either the nonlinearmodel of the underactuated systems is transformed into an input output formand then an integral manifold is devised for the control design purpose or an integral manifold is defined directly for the concerned class. Having defined the integral manifolds discontinuous control laws are designed which are capable ofmaintaining slidingmode fromthe very beginning. The closed loop stability of these systems is presented in an impressive way. The effectiveness and demand of the designed control laws are verified via the simulation and experimental results of ball and beam system.